The Addition of Resveratrol-Loaded Emulsions to Yogurts: Physicochemical Characterization, In Vitro Bioaccessibility and NMR-Based Nutritional Profiles - Zihui Shi; Huan Chen; Junbo He; Weinong Zhang; Hong Lin (Foods, 2024)
In this study, resveratrol-loaded nano-emulsions were added to yogurts, improving the physicochemical properties and functional factors and realizing the development of nutrient-fortified yogurt. Yogurts added with free resveratrol (Y-R), resveratrol-loaded emulsions stabilized by sodium caseinate (Y-NN), decaglycerol monooleate (Y-DN), and sodium caseinate-decaglycerol monooleate (Y-DND) were evaluated for their physicochemical properties, including pH, titratable acidity, syneresis, and textural parameters, with 5-day intervals for 15-day storage. The resveratrol retention rate was analyzed in the Y-R, Y-NN, Y-DN, and Y-NDN groups during 15 days of storage. The dynamic bioaccessibility of resveratrol and the NMR-based nutritional profile of yogurt in the Y-R, Y-NN, Y-DN, and the Y-NDN group were investigated after in vitro digestion. The results demonstrated that the addition of resveratrol emulsion decreased the hardness of yogurt while evaluating its titratable acidity and water-holding capacity, which were characterized by high stability. The stability of resveratrol added in the form of an emulsion was significantly higher than that of the free form. Compared with the other groups, the yogurt formulated with sodium caseinate/decaglycerol monooleate (NaCas/DGMO) emulsion showed the highest resveratrol retention rate, about 70%. In vitro digestion showed that encapsulation effectively and persistently improved the dynamic bioaccessibility of resveratrol. Additionally, NMR-based nutritional profile analysis before and after in vitro digestion demonstrated that resveratrol emulsion nutritional fortification promoted the release of nutrients, improving the nutritional value of yogurt. These findings offered theoretical guidance and technical support for the use of resveratrol nano-emulsions in yogurt.